An Indication of Anisotropy in Arrival Directions of Ultra-high-energy Cosmic Rays through Comparison to the Flux Pattern of Extragalactic Gamma-Ray Sources - Aab, A.; Allekotte, Ingomar; Almela, Daniel Alejandro; Andrada, B.; Bertou, Xavier Pierre Louis; Botti, Ana Martina; Cancio, A.; Contreras, F.; Etchegoyen, Alberto; Figueira, Juan Manuel; Fuster, Alan Ezequiel; Golup, Geraldina Tamara; et al. (IOP Publishing, 2018)
Fil: Aab, A.. Radboud University Nijmegen; Países Bajos